Identification of a novel B-cell epitope of the African swine fever virus p34 protein and development of an indirect ELISA for the detection of serum antibodies - Tian, Yuanyuan; Liang, Chao; Zhou, Jingming; Sun, Fanglin; Liu, Yankai; Chen, Yumei; Zhu, Xifang; Liu, Hongliang; Ding, Peiyang; Liu, Enping; Zhang, Ying; Wu, Sixuan; et al. (Frontiers in Microbiology, 2024)
African swine fever (ASF) is a viral disease caused by African swine fever virus that can be highly transmitted and lethal in domestic pigs. In the absence of vaccine, effective diagnosis is critical for minimizing the virus's spread. In recent years, with the decline of African swine fever virus virulence, antibody detection has become an important means of detection. ASFV nucleocapsid protein p34 is a mature hydrolytic product of pp220, which is highly conserved and has high content in the structural protein of the virus. Prokaryotic cells were chosen to generate highly active and high-yield p34 protein, which was then used as an antigen for producing mouse monoclonal antibodies. The B cell epitope 202 QKELDKLQT 210 , which was highly conserved and found on the surface of the p34 protein, was first identified by anti-p34 monoclonal antibody utilizing the peptide scanning technique and visualized in helix. This supported the viability of p34 protein detection even further. In addition, we established an indirect ELISA assay based on p34 to detect ASFV antibodies. The coincidence rate of this method with commercially available kits was shown to be 97.83%. Sensitivity analysis revealed that it could be detected in serum dilution as low as 1:6400, and there was no cross-reaction with other prevalent porcine epidemic diseases CSFV, FMDV, PRRSV and PCV2. In summary, the established ELISA method and anti-P34 monoclonal antibody have demonstrated that p34 protein has a promising application prospect for the detection of African swine fever antibodies.